2016
DOI: 10.1590/1678-4324-2016150485
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of LPS on the Viability and Proliferation of Human Oral and Esophageal Cancer Cell Lines

Abstract: The esophagus and mouth tumors are very frequent malignancies worldwide. Lipopolysaccharides (LPS) are capable of regulating gene expression of pro-inflammatory cytokines by binding to toll-like receptor 4 (TLR4). Recent studies show that LPS can increase the migration ability of human esophageal cancer cell line HKESC-2 by increasing its adhesion properties. However, the effect of LPS has not been tested on viability of human esophageal and oral cancer cells. This study aimed to determine the action of LPS on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…This observation is not always in agreement with the previous reports. Thus, P. gingivalis LPS, at concentrations similar to that used in our study, enhanced the proliferation/viability of primary human oral epithelial cells [ 43 ], but did not affect that of oral squamous carcinoma cells [ 44 ]. TNF-α at a concentration of 100 ng/mL was shown to induce the apoptosis of primary gingival epithelial cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is not always in agreement with the previous reports. Thus, P. gingivalis LPS, at concentrations similar to that used in our study, enhanced the proliferation/viability of primary human oral epithelial cells [ 43 ], but did not affect that of oral squamous carcinoma cells [ 44 ]. TNF-α at a concentration of 100 ng/mL was shown to induce the apoptosis of primary gingival epithelial cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS is found in the cell wall of Gram-negative bacteria. Previous studies have shown that P. gingivalis LPS tend to increase the viability of oral cancer cells [3]. Studies of the tumour microenvironment have shown that macrophages demonstrate increased IL-6 and CD14 expression and increased nitric oxide secretion after the stimulation of LPS [2].…”
Section: Introductionmentioning
confidence: 99%
“…LPS treatment induces Ca 2+ entry in cancer cells in a TLR4-dependent manner, resulting in a chronic elevation of basal intracellular calcium levels [7]. Previous studies have shown that Porphyromonas gingivalis LPS tend to increase the viability of oral cancer cells [8], while within the tumour microenvironment, macrophage expression of IL-6 and CD14 is increased as well as free radical secretion [7]. Bacterial infection has been shown to be associated with chronic inflammation, anti-apoptotic activity, and pro-proliferative activities [9].…”
Section: Introductionmentioning
confidence: 99%